Atlantic water inflow in the early Holocene Northwest Passage marked by planktonic foraminifera (Neogloboquadrina pachyderma) - Pieńkowski, Anna J.; Cage, Alix; Furze, Mark F.A.; Figueiredo Martins, Ana Sílvia de; England, John H.; McLean, Brian; Blasco, Steve (My University, 2015)
Four marine piston cores from the central Canadian Arctic Archipelago (CAA), investigated for sedimentology, micropalaeontology, and biogeochemistry (52 AMS radiocarbon dates), uniformly show the prominent early Holocene (˜10 cal ka BP) appearance of planktonic foraminifera immediately following deglaciation.
Presented on May 10–13, 2015 at the 45th International Arctic Workshop held on the campus of the University of Bergen, Norway.